ESMO - Magnitude of Clinical Benefit Scale V.1.0 questions and answers - Cherny, N I (ESMO Open, 2016)
The ESMO Magnitude of Clinical Benefit Scale (ESMO-MCBS) is a standardised, generic, validated tool to stratify the magnitude of clinical benefit that can be anticipated from anticancer therapies. The ESMO-MCBS is intended to both assist oncologists in explaining the likely benefits of a particular treatment to their patients as well as to aid public health decision makers' prioritise therapies for reimbursement. From its inception the ESMO-MCBS Working Group has invited questions and critiques to promote understanding and to address misunderstandings regarding the nuanced use of the scale, and to identify shortcomings in the scale to be addressed in future planned revisions and updates. The ESMO-MCBS V.1.0 has attracted many questions regarding its development, structure and potential applications. These questions, together with responses from the ESMO-MCBS Working Group, have been edited and collated, and are herein presented as a supplementary resource.